Time, space, and the new media machine of the terrorphone - Armitage, John (Approaching Religion, 2013)
In this short article, the author is concerned with how the contemporary form of the telephone, a new media machine which was of deep-rooted significance for Marshall McLuhan, promotes our obsession with forms of shared participation and social implosion. The author argues that the form of the telephone involves a complex abolition of our sense of space, interwoven with unexpected socio-cultural effects, which then create new subjectivities as well as new forms of decentralization that are intuited but not fully understood. To politicize these effects, and following the revelations of the American whistleblower Edward Snowden, the author identifies the form of the mobile telephone as a new form of media and argues that it is no longer an ‘extension of man’, as McLuhan suggested, but an extension of the US State, which is producing new forms of socio-cultural collapse. The author then explores how the remote-controlled time and space of what he calls the ‘terrorphone’ cultivates, among other things, the contemporary visualization of speech. Finally, he questions the desirability of unrelenting mobile telephone interaction as our only ‘intelligent’ choice today when such interaction is, contrary to McLuhan, not a great extension of our central nervous system, but in fact a danger to it.